2021
DOI: 10.18535/ijsrm/v9i11.em11
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Emotional Intelligence on Work Motivation. An Empirical Assessment

Abstract: The paper investigated the association between emotional intelligence and work motivation among employees of organisations to determine whether emotional intelligence differences exist in work motivation, and to assess the nature of the association between emotional intelligence and work motivation. A sample of 140 respondents was selected through the convenience sample method for the primary data collection. A set of questionnaires developed by the researcher was used to collect data from the respondents. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Several types of data are available in a business activity, by which daily progress report of a business activity is gathered properly. Every business activity always tries to maintain data protection methods in a significant way to be up to date [5]. Data protection is one of key challenges of digital transformation in global market.…”
Section: Resultsmentioning
confidence: 99%
“…Several types of data are available in a business activity, by which daily progress report of a business activity is gathered properly. Every business activity always tries to maintain data protection methods in a significant way to be up to date [5]. Data protection is one of key challenges of digital transformation in global market.…”
Section: Resultsmentioning
confidence: 99%
“…There is a study that shows a statistically significant correlation between safe space measurements and the parameters of an individual's motivational orientation (Blynova et al, 2022). The relationship between emotional intelligence and labor motivation was investigated by S. Mohammed (2021). The study found that the development of emotional intelligence is a factor in the high levels of labor motivation.…”
Section: вступmentioning
confidence: 99%
“…Є дослідження, в яких встановлено статистично достовірні кореляційні зв'язки вимірів безпечного простору з параметрами мотиваційної спрямованості особистості (Blynova et al, 2022). S. Mohammed (2021) Hypotheses. It is assumed that all the parameters of emotional intelligence have statistically significant correlations with measurements of motivation.…”
Section: вступunclassified
“…This article explores the critical role of accountability in cybersecurity, addressing the need for robust monitoring, clear communication, and consequence management to fortify the organization's resilience against evolving cyber threats. Implementing systems to track user activity, ensuring that employees adhere to established security policies and guidelines in their digital interactions (Mohammed, 2021). Deploying advanced network monitoring tools to detect unusual patterns of behavior, potential intrusions, or deviations from normal cybersecurity protocols.…”
Section: Accountability In Cybersecuritymentioning
confidence: 99%